Perancangan dan Implementasi Filter Pasif EMI pada Sistem Auto Light Dimmer - Harpawi, Noptin; Lizani Hasmi, Nashra; Wira Indani (Politeknik Caltex Riau, 2024)
Indoor farming requires a substitute for sunlight for its growth, therefore a system was created to control the light intensity used for indoor farming using the BH1750 Sensor which has an accuracy level of 94.6% and an AC Light Dimmer as a PWM Module. It is important to remember that AC Light Dimmers regulate light intensity by cutting off some of the sinusoidal waves from the AC electric current, and this can produce side effects such as noise or electromagnetic interference (EMI) in electrical lines. In the noise conducted emission test on the AC Light Dimmer, a noise value of 80.33dBµV was obtained, which is far from the CISPR 22 Class B standard value, so a passive EMI filter with the Low Pass Filter (LPF) type was designed to be able to reduce the conducted emission noise. The passive EMI filter designed and tested has an effective dampening response even though there is a shift in the cut-off frequency of 28.7KHz from that obtained in the calculations. The Passive EMI Filter designed is capable of reducing noise conducted emissions produced by AC Light dimmers by 80.33dBµV to 26.46dBµV and produces excellent attenuation of up to 53.87dB and meets the specified standards (CISPR22 Class B).